A Systematic Review of Metaheuristic Approaches to the Deployment Problem in Wireless Sensor Networks - Abdullahi, Shamsu; Qabasiyu, Muhammad Garzali; Danyaro, Kamaluddeen Usman; Zakari, Abubakar; Maitama, Jaafar Zubairu; Abubakar Imam, Abdullahi (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2025)
Wireless Sensor Networks (WSNs) are widely applied in various fields, such as healthcare, security, agriculture, and education, where they simplify complex tasks and enable advanced monitoring. However, effective deployment remains a critical challenge in WSNs, affecting coverage, connectivity, energy efficiency, and network lifespan. Despite the importance of deployment optimization, no comprehensive Systematic Literature Review (SLR) has been conducted on metaheuristic approaches to address this challenge. This paper systematically reviews the demographic distribution, state-of-the-art metaheuristic solutions, and experimental evaluation methods related to the WSN deployment problem. A total of 112 studies were analyzed to address key research questions. Our findings provide a structured overview of current methodologies and identify significant research gaps. Key challenges observed include limited availability of open datasets, over-reliance on simulation validation, and the lack of comprehensive performance metrics such as latency and delay. These insights suggest future research directions for further optimizing WSN deployment.